Care for older people between state and family - Hlebec, Valentina (Teorija in praksa, 2014)
As in other countries, the family is the main provider of care for older people in Slovenia. However, with the development of social home care in the 1990s, an important addition to informal care has been introduced. The first Slovenian representative survey of social home care users (2013) has been used to assess the care arrangements among users of social home care and the impact of both need across activities of daily living and the availability of informal care networks on care arrangements. The level of functional impairment (an indicator of need) and household composition (an indicator of availability of crucial elements of an informal care network) have proved to be indicative of the levels of usage of particular care arrangements; distinguishing between informal care only, formal care only, and mixed care.
Keywords: Community care; Older people; pomoč na domu; Slovenia; Slovenija; Social support; Socialna opora; Socialno skrbstvo; socialno varstvo; Starostniki